Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/jac/dku466
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporinases associated with outer membrane vesicles released by Bacteroides spp. protect gut pathogens and commensals against β-lactam antibiotics

Abstract: ObjectivesTo identify β-lactamase genes in gut commensal Bacteroides species and to assess the impact of these enzymes, when carried by outer membrane vesicles (OMVs), in protecting enteric pathogens and commensals.MethodsA deletion mutant of the putative class A β-lactamase gene (locus tag BT_4507) found in the genome of the human commensal Bacteroides thetaiotaomicron was constructed and a phenotypic analysis performed. A phylogenetic tree was built from an alignment of nine Bacteroides cephalosporinase prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 42 publications
(47 reference statements)
0
113
0
Order By: Relevance
“…Previous studies on the multidrug-resistant species S. maltophilia showed a clear vesiculation response to b-lactam antibiotics (Devos et al, 2015), and the secreted OMVs were proven to degrade b-lactams in the extracellular environment . Indeed, several other studies showed that OMV biogenesis can be induced in response to b-lactam stress, linking this phenomenon to b-lactam resistance (Ciofu et al, 2000;Schaar et al, 2011;Lee et al, 2013;Stentz et al, 2015). However, vesicle formation has also been observed for antibiotics that do not directly interfere with cell wall synthesis, for example the DNA damaging fluoroquinolone ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the multidrug-resistant species S. maltophilia showed a clear vesiculation response to b-lactam antibiotics (Devos et al, 2015), and the secreted OMVs were proven to degrade b-lactams in the extracellular environment . Indeed, several other studies showed that OMV biogenesis can be induced in response to b-lactam stress, linking this phenomenon to b-lactam resistance (Ciofu et al, 2000;Schaar et al, 2011;Lee et al, 2013;Stentz et al, 2015). However, vesicle formation has also been observed for antibiotics that do not directly interfere with cell wall synthesis, for example the DNA damaging fluoroquinolone ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella , however, can catabolize this liberated monosaccharide, and access to it supports the pathogen’s proliferation in the gut [78]. B. thetaiotaomicron also produces a beta-lactamase that protects the bacteria from beta-lactam antibiotics, including Salmonella [79]. Another microbe that helps Salmonella to degrade mucin is Akkermansia muciniphila , which exacerbates Salmonella -induced intestinal inflammation by disturbing host mucus homeostasis [80].…”
Section: Figurementioning
confidence: 99%
“…The partial degradation of OMV-associated OXA-58 by proteinase K indicated that some of the OXA-58 is attached to the outer surface of the OMVs. Although Moraxella catarrhalis ␤-lactamase was found within OMVs, a Bacteroides cephalosporinase was found on the outer surface of OMVs (29). This proteinase K-susceptible OXA-58 may also arise from the breakdown of OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…OMV-associated ␤-lactamase release has been observed in Pseudomonas aeruginosa (34), M. catarrhalis (10), and Bacteroides species (29). Previously, an Acinetobacter-derived cephalosporinase was identified in A. baumannii OMVs, but its function was not characterized (11).…”
Section: Discussionmentioning
confidence: 99%